2020
DOI: 10.1177/1526602820923827
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Midterm Outcomes of Endovascular Aneurysm Repair in Octogenarians From the ENGAGE Registry

Abstract: Purpose: To assess periprocedural results and secondary endovascular procedure outcomes over 5 years in patients aged ≥80 vs <80 years undergoing endovascular aneurysm repair (EVAR). Materials and Methods: Data from the Endurant Stent Graft Natural Selection Global post-market registry (ENGAGE) were used for the analyses. A total of 1263 consecutive patients were enrolled in the prospective, observational, single-arm registry and divided into 2 groups according to age: ≥80 years (290, 22.9%) and <80 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
(28 reference statements)
2
4
0
Order By: Relevance
“… 19 Unsurprisingly, the analysis at 5 years from the ENGAGE (Endurant stent graft natural selection global postmarket) registry among only octogenarians after EVAR found that both ASA III and ASA IV vs ASA I were associated with increased all-cause mortality. 20 Consistent with these prior findings for endovascular aneurysm repair patients, we have extended the current understanding and report that a higher ASA class is also independently associated with increased all-cause mortality and complications in the long term in patients with acute complicated type B dissection and traumatic dissection. We posit that in a more heterogeneous series, ASA class would continue to remain important.…”
Section: Discussionsupporting
confidence: 88%
“… 19 Unsurprisingly, the analysis at 5 years from the ENGAGE (Endurant stent graft natural selection global postmarket) registry among only octogenarians after EVAR found that both ASA III and ASA IV vs ASA I were associated with increased all-cause mortality. 20 Consistent with these prior findings for endovascular aneurysm repair patients, we have extended the current understanding and report that a higher ASA class is also independently associated with increased all-cause mortality and complications in the long term in patients with acute complicated type B dissection and traumatic dissection. We posit that in a more heterogeneous series, ASA class would continue to remain important.…”
Section: Discussionsupporting
confidence: 88%
“…Pini et al 4 have shown that an American Society of Anesthesiologists (ASA) score of IV is an independent predictor of 30-day mortality in octogenarians undergoing EVAR; however, the most important finding of that study is that several factors other than ASA IV, such as peripheral artery disease, chronic obstructive pulmonary disease, and chronic renal disease, play significant roles in midterm survival. The outcomes reported by Mwipatayi and colleagues 1 are consistent with these findings, since several factors were found to predict all-cause mortality. It is also interesting to observe that quality of life has an important role in late survival.…”
supporting
confidence: 71%
“…The study from Mwipatayi et al 1 in the October 2020 issue of the JEVT is important for a variety of reasons. First of all, it reports an interesting subanalysis of the prospective, observational, single-arm ENGAGE registry, which involves almost 80 centers worldwide and represents a clear image of the real-world performance of a modern endovascular solution for most abdominal aortic aneurysms (AAA).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, 80% of older patients with AAA are successfully treated with endovascular therapy 7 . Data on EVAR in octogenarian patients are contradictory, and although the success rate of the procedure is high, post-procedural and long-term complications are often higher when compared to younger patients 1,[8][9][10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%